The aesthetics of the open space in the poetry of Mahmoud Sami Al-Baroudi - Sabri, Mohamed; Jumaa, Muhammad (Humanities Journal of University of Zakho, 2022)
The aesthetics of the open space in the poetry of Mahmoud Sami Al-Baroudi Summary: The aesthetics of open spaces in Mahmoud Sami Al-Baroudi’s poetry is an interesting phenomenon, and this phenomenon is formed from the large concentration on open spaces in his poetry. The place is one of the important elements that contribute and shape the aesthetics of the modern poetic text, and when studying Al-Baroudi’s Diwan, we note that the place was present in multiple aesthetic aspects that the poet employed to express the psychological attitudes and concerns he lived in those places. The study was based on the poet's psychological and emotional relationship with the place, through his description of the aesthetics of open spaces in a poetic language full of descriptions and similes, and suggestive connotations that overflow with poetic meanings. As well as describing the aesthetics of the village, and the living and silent nature, with all its data of orchards, meadows, green meadows and birds, and with these descriptions he approaches the pre-Islamic poem in his view of the place, as he mentioned the aesthetics of hostile places such as the desert, describing the roads with all their temptations and urging to leave And travel, which was formed in the poet as a result of his adherence to the psychological repercussions of the place, and his portrayal of the challenges he encounters in the places he passes through, he does what the ancient poets do in describing the fifi and the desert, in a precise poetic language, in an attempt to clarify and draw the aesthetics of open spaces, and to clarify their connotations and aesthetics. Keywords: (aesthetics, al-Baroudi, poetry, nature, desert, place, significance